2020
DOI: 10.5114/bta.2020.92929
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of plant growth-promoting stress-tolerant endophytes screened from Bougainvillea glabra for the growth of Triticum aestivum L. and Zea mays

Abstract: Globally, more than 5.2 billion hectares of farming fields are damaged through erosion, salinity, and soil deterioration. Salt stress-tolerant bacteria have plant growth-promoting (PGP) characteristics that can be used to overcome environmental stresses. Isolation and screening of salt-tolerant endophytes from Bougainvillea glabra were achieved through surface sterilization of leaves, followed by their cultivation on 0.5% NaCl-supplemented media. The performance of isolates for indole acetic acid (IAA) product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A previous study (Akter and Oue 2018) showed that microbial inoculants improved root growth which encouraged plant growth and nutrient access to plant roots, i.e., nitrogen (N), phosphorus (P), and potassium (K). In an earlier study, Karnwal (2020) reported the beneficial effects of salt-tolerant PGP bacterial isolates BoGl17 on the growth of Triticum aestivum L. var. HD 2687 and Zea mays var.…”
Section: Pot Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study (Akter and Oue 2018) showed that microbial inoculants improved root growth which encouraged plant growth and nutrient access to plant roots, i.e., nitrogen (N), phosphorus (P), and potassium (K). In an earlier study, Karnwal (2020) reported the beneficial effects of salt-tolerant PGP bacterial isolates BoGl17 on the growth of Triticum aestivum L. var. HD 2687 and Zea mays var.…”
Section: Pot Experimentsmentioning
confidence: 99%
“…The Food and Agriculture Organization (FAO) and United Nations Environment Programme (UNEP) statistics have reported that 5.2 billion hectares of agricultural land are currently ruined through erosion, salinity and deterioration of soil (Numan et al 2018). Out of this, 0.4 billion hectares of land is ruined globally due to salinity (20% of agricultural and 50% of croplands) and threaten agricultural productivity (Karnwal 2020). To overcome the negative impact of the salt environment, researchers are developing various strategies to produce salt stress-resistant plant varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial isolates intended for the current research were isolated and identified from B. glabra rhizosphere grown at the Bhojia Institute of Life Sciences, Budh, Baddi, Himachal Pradesh, India (located at latitude 30.952802 and longitude 76.776914) as explained in an earlier investigation of Karnwal (2017). The rhizospheric soil samples were serially diluted up to 10 !6 , and 0.1 ml of suspension from the 10 !6 dilution was spread onto a modified nutrient agar medium (NAM) enriched with 4% salt (NaCl) as described by Karnwal (2020). The plates were incubated for up to 72 h at 28 ± 1EC in dark.…”
Section: Isolation Of Bacteria From B Glabra Rhizospherementioning
confidence: 99%
“…The surface-sterilized seeds were immersed in a bacterial suspension and rotated at 150 rpm for 2 h at 28EC. The seeds were then air-dried in a laminar airflow hood for 60 min (Karnwal, 2020). Ten seeds per crop were placed on a sterile moistened Whatman No.…”
Section: Seed Inoculation Studymentioning
confidence: 99%
See 1 more Smart Citation